Sense of Place and Social Anxiety Relations of New Comers of Raden Intan State Islamic University, Lampung - Jatmiko, Agus (Universitas Islam Negeri Raden Intan Lampung, 2018)
Migration is a form of migration that can be seen in several regions in Indonesia. Wandering not only occurs in finding work but also in students who will continue their education in college. Migrant students will experience situations that are different from life in their place of origin, for example differences in culture, language and communication. As social beings we cannot be separated from interaction, where in this interaction a special feeling will be formed that is received by humans produced from a place with various elements in it, including those who live in it, this special feeling is called the sense of place . In interacting not all individuals feel safe and comfortable, but there are also those who have feelings of anxiety, fear, or worry about the surrounding environment, anxiety or concern related to social situations is called social anxiety. This study uses quantitative research methods with the subject of 90 students from Tarbiyah and Teaching Faculty of Lampung State Islamic University as chosen by using the sample technique, namely purposive sampling. Data collection uses a questionnaire about the variable sense of place and social anxiety variables . Hypothesis testing in this study uses Product Moment correlation analysis . The conclusion of the study is that there is a relationship between the sense of place and social anxiety on students from the Tarbiyah Faculty of Education and Teacher Training at the State Islamic University Raden Intan Lampung.